An adhoc UW image colour correction method and the impact on image feature matching & SfM-MVS 3D reconstruction - Vlachos, Marinos; Skarlatos, Dimitrios; Calantropio, Alessio; Chiabrando, Filiberto (My University, 2022)
The problem of colour correction of underwater images concerns not only surveyors, who primarily use images for photogrammetric purposes, but also archaeologists, marine biologists, and many other experts of different disciplines whose aim is to study objects and lifeforms underwater. For this reason, this study aims to address and quantify the impact of an ad-hoc underwater image restoration algorithm regarding image feature matching and 3D reconstruction of the scene. The datasets used for the purpose of this study consist of the original and colour corrected images captured in two different sites located in Cyprus with different depths and different water conditions. The images were colour corrected following a simple mathematical model that utilizes the scene's geometry while considering also the absorption and backscattering of light in order to restore the missing colour information.
Keywords: Colour restoration; Feature matching; Underwater photogrammetry; 3D point clouds